Microsoft Windows 7 unleashed - McFedries, Paul (Sams, 2010)
Covers Release Candidate of Windows 7. With purchase of this book you will get a free online edition written on final product. See product registration ad in back of book for details. Microsoft® Windows 7 Unleashed gives IT professionals, serious power users, and true geeks the powerhouse Windows 7 tweaks, hacks, techniques, and insights they need: knowledge that simply can't be found anywhere else. Top Windows expert Paul McFedries dives deep into Windows 7, returning with the most powerful ways to handle everything from networking to administration, security to scripting. McFedries begins with advanced customization, covering everything from startup/shutdown to the file system. He introduces new ways to tune Windows 7 performance, police Windows via Group Policies, tweak the Registry, make the most of Windows 7s management tools, and control Windows 7 from the command line. You'll find thorough coverage of securing Windows 7, including detailed guidance on web and email security and hardening both wireless and wired networks. You'll also discover better ways to troubleshoot devices, networks, and startup; add Macs to Windows networks; and automate Windows administration with state-of-the-art scripting techniques. This book is packed with expert tips, tricks, and troubleshooting techniques drawn from McFedries' unsurpassed Windows experience. If you want maximum value and performance from your Windows 7 PCs, you won't find a more valuable resource. Customize everything about Windows 7: IE8, startup/shutdown, file systems, the Start menu, Taskbar, and more Systematically monitor, tune, and optimize Windows performance-including practical techniques for accelerating startup Set up an easy, automated 9-Step maintenance schedule for any Windows 7 PC Unleash Windows 7s power user tools, including Group Policies, the Registry, MMC, and the command line Secure Windows 7 with security settings: auto-lock, Windows Firewall, Windows Defender, parental controls, BitLocker encryption, and more Protect your web privacy with Windows 7s new InPrivate Browsing Solve problems with Windows 7, startup, networking, and hardware Set up reliable Windows 7 networks, and manage them efficiently Safely provide remote access and VPN connectivity Use Windows 7 as a Web server Program the Windows Scripting Host and Windows PowerShell ON THE WEB: Free Online Edition! When Microsoft releases the final product, you can get an updated edition of this book absolutely free! All examples and source code presented in this book $49.99 USA / $59.99 CANz.